Vivência em rede: uma etnografia das práticas sociais de informação dos usuários de redes sociais na internet - Nunes, Jefferson Veras [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Treat about how the phenomenon of social networking sites affects the contemporary informational scenario, transforming everyday practices and experiences of individuals with regard to the production, consumption and sharing of information in digital space. Problematizes how the expression society of information has been referenced to characterize a form of social organization based on the information technology paradigm. Then discusses the current structure of the media system, focusing since the formation of a mass society, to the ubiquity of digital information in urban areas, with the aim of demonstrating that socio-cultural scene is marked by an increasingly converging means, as well as languages. Accordingly, discusses the internet as a kind of media marked by computer-mediated communication, in which different forms of media are articulated, giving rise to system based on network interconnection. Through the notion of network underscores the fact that the social context of networking sites consists of complex associations between humans and technologies, aiming to empirical research attend more to the hybrid nature of these relationships, and less for their infrastructural aspect. For empirical verification, purposes qualitative research, using ethnographic method, with the intention of supporting the argument that social media has the ability to affect the everyday experiences of individuals, changing informational scenario. As empirical field elects Facebook, choosing because it is characterized as the social network site most used in Brazil and in several other countries. Conducts interviews with twelve users of Facebook, still using the participant observation, examinee the interactions among netizens as well as the ways in which they relate to the information and the site through the available tools. Accordingly, concludes that each one of the informational practices observed point aspects of how information is and is at the...

Trata sobre como o fenômeno das redes sociais na internet afeta o cenário informacional contemporâneo, transformando as práticas e experiências cotidianas dos indivíduos no tocante à produção, consumo e compartilhamento da informação no espaço digital. Problematiza como a expressão sociedade da informação tem sido referenciada para caracterizar um formato de organização social baseado no paradigma tecnológico da informação. Em seguida, aborda a composição contemporânea do sistema de mídia, discutindo desde a formação de uma sociedade de massa, até a ubiquidade da informação digital no espaço urbano, com o objetivo de demonstrar que a cena sociocultural é marcada cada vez mais por uma convergência de meios, assim como de linguagens. Nesse sentido, discute a internet como um tipo de mídia marcada pelo despontar da comunicação mediada por computador, no qual diferentes meios de informação e comunicação se articulam, dando origem a um sistema baseado na interligação em rede. Através da noção de rede ressalta o fato de que o contexto das redes sociais na internet é formado por complexas associações entre humanos e tecnologias, almejando com a pesquisa empírica atentar mais para o caráter híbrido dessas relações, e menos para o seu aspecto infraestrutural. Como estratégia metodológica, realiza uma pesquisa de cunho qualitativo, recorrendo ao método etnográfico, com a intenção de confirmar a tese de que as redes sociais na internet têm a capacidade de afetar as experiências cotidianas dos indivíduos, reconfigurando o cenário informacional contemporâneo. Como campo empírico adota o Facebook, escolhendo-o por se caracterizar como o site de redes sociais mais utilizado no Brasil, bem como em vários outros países. Assim, além de entrevistas realizadas com doze usuários do Facebook, recorre, ainda, à observação participante, atentando às interações entre os internautas, bem como às...
Keywords: Sites da Web; Redes sociais; Cibercultura; Ciência da informação; Cyberculture